2018
DOI: 10.3390/s18092798
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Stress in Cotton (Gossypium hirsutum L.) Caused by Aphids Using Leaf Level Hyperspectral Measurements

Abstract: Remote sensing can be a rapid, accurate, and simple method for assessing pest damage on plants. The objectives of this study were to identify spectral wavelengths sensitive to cotton aphid infestation. Then, the normalized difference spectral indices (NDSI) and ratio spectral indices (RSI) based on the leaf spectrum were obtained within 350–2500 nm, and their correlation with infestation were qualified. The results showed that leaf spectral reflectance decreased in the visible range (350–700 nm) and the near-i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 35 publications
3
27
0
1
Order By: Relevance
“…However, the lack of an effective means for analyzing hyperspectral information makes it difficult to conduct systematic quantitative analysis of hyperspectral indices on all possible two-band combinations (from 350 nm to 2500 nm), precise feature bands indicating biochemical components in plants might therefore not be fully explored and utilized [26]. Therefore, the development and optimization of techniques such as a spectral vegetation index that requires only limited data is of great significance and practical value in monitoring the physiological and ecological parameters of plants [27]. Studies have shown that the paired spectral vegetation index, a method that minimizes interference from LAI and background reflectance, can be used to estimate leaf chlorophyll concentrations [28].…”
Section: Discussionmentioning
confidence: 99%
“…However, the lack of an effective means for analyzing hyperspectral information makes it difficult to conduct systematic quantitative analysis of hyperspectral indices on all possible two-band combinations (from 350 nm to 2500 nm), precise feature bands indicating biochemical components in plants might therefore not be fully explored and utilized [26]. Therefore, the development and optimization of techniques such as a spectral vegetation index that requires only limited data is of great significance and practical value in monitoring the physiological and ecological parameters of plants [27]. Studies have shown that the paired spectral vegetation index, a method that minimizes interference from LAI and background reflectance, can be used to estimate leaf chlorophyll concentrations [28].…”
Section: Discussionmentioning
confidence: 99%
“…In parallel with the chlorophyll fluorescence measurements, canopy reflectance spectra were measured according to the methods of Chen et al (2018) [24] by using a FieldSpec UV/VNIR spectraradiometer (ASD Inc., Boulder, Colorado, USA) over the 325-1075 nm wavelength range at 3 nm intervals. The 3 nm intervals are automatically interpolated to 1nm intervals by this instrument.…”
Section: Canopy Reflectance Measurementsmentioning
confidence: 99%
“…Remote sensing has been used to detect stress caused by arthropod herbivory in a variety of plant species, such as maize [17], soybean [4], rice [18,19], wheat [20], peach trees [12,21], cotton [22] and potato [23].…”
Section: Introductionmentioning
confidence: 99%